2023
DOI: 10.1101/2023.08.28.23294607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of the Diagnostic Performance from Patient’s Medical History and Imaging Findings between GPT-4 based ChatGPT and Radiologists in Challenging Neuroradiology Cases

Daisuke Horiuchi,
Hiroyuki Tatekawa,
Tatsushi Oura
et al.

Abstract: PurposeTo compare the diagnostic performance between Chat Generative Pre-trained Transformer (ChatGPT), based on the GPT-4 architecture, and radiologists from patient’s medical history and imaging findings in challenging neuroradiology cases.MethodsWe collected 30 consecutive “Freiburg Neuropathology Case Conference” cases from the journal Clinical Neuroradiology between March 2016 and June 2023. GPT-4 based ChatGPT generated diagnoses from the patient’s provided medical history and imaging findings for each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This study is the first attempt to evaluate ChatGPT's ability to interpret actual clinical radiology reports, rather than from settings like image diagnosis quizzes. The majority of previous research (6)(7)(8)(9)(10)(11)(12)(17)(18)(19)(20)(21) suggested the utility of ChatGPT in diagnostics, but these relied heavily on hypothetical environments such as quizzes from academic journals or examination questions (26). This approach can lead to a cognitive bias since the individuals formulating the imaging findings or exam questions also possess the answers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study is the first attempt to evaluate ChatGPT's ability to interpret actual clinical radiology reports, rather than from settings like image diagnosis quizzes. The majority of previous research (6)(7)(8)(9)(10)(11)(12)(17)(18)(19)(20)(21) suggested the utility of ChatGPT in diagnostics, but these relied heavily on hypothetical environments such as quizzes from academic journals or examination questions (26). This approach can lead to a cognitive bias since the individuals formulating the imaging findings or exam questions also possess the answers.…”
Section: Discussionmentioning
confidence: 99%
“…Within the realm of LLMs, the GPT series, in particular, has gained significant attention. Many applications have been explored within the field of radiology (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Among these, the potential of GPT to assist in diagnosis from image findings is noteworthy (18)(19)(20) because such capabilities could complement the essential aspects of daily clinical practice and education.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations